(Google-)Knowing Economics. (3rd May 2020) - Macknight, Vicki; Medvecky, Fabien
ABSTRACT: How is economics made public? Specifically, how is economics made public on Google? Here we explore a methodological problem – studying google-knowing – and simultaneously explore the more pragmatic problem of the public-making of economics. We argue there has been very little attempt either to make economics public or to understand what is currently in the public sphere about economics. This is especially stark when compared to other knowledge contributors to society, like science. We start to remedy this gap by using a methodological figure: the google-knower. Google-knowing is central to how knowledge is created and circulated in society in the digital age and raises a range of questions at the heart of how we understand and make sense of our (economic) world. In this paper, we make common cause with google-knowers by searching on Google for economics. We find a picture of a discipline marked on the one hand by secrecy and gatekeeping and on the other by an insistence that it is not boring. We also argue that using the figure of the google-knower as a methodological tool offers insights into classic questions in epistemology, such as objectivity, knowledge as a commodity, a knowers' identity and expertise.